English and Portuguese consonant clusters: contrasts and challenges - Madureira, Sandra (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
Consonant clusters occur both in Portuguese and English. However, clusters are more productive in English than in Portuguese and there are sequences which are only found in English.This study focuses on the contrasts between American English and Brazilian Portuguese consonant clusters and on three strategies Brazilian learners tend to apply when producing them: adding the high front vowel (epenthesis) between the consonants in the clusters, discarding consonants, or introducing phonetic changes. The relevance of introducing English clusters to Brazilian learners of English is pointed out and discussed under the framework of the Speech Learning Model (SLM).